Motivational Interviewing for Poorly Controlled Type 2 Diabetics in a Rural South African Community (Archives of Clinical and Medical Case Reports, 2018)
Difficulty adhering to lifestyle changes required for effective management is rife among patients with Type 2 Diabetes Mellitus (T2DM). Motivational interviewing may prove a useful tool for healthcare providers when supporting patients. Thirteen poorly controlled T2DM patients, 11 females and 2 males, took part in the study. A qualitative design with semi-structured interviews was used and the data was analysed by means of thematic analysis. Themes explored included Stumbling blocks to change, awareness of difficulties, making changes, and the role of motivational interviewing. Motivational Interviewing was received positively and provided useful information, which will help to understand the needs of the diabetic in a rural community as well as suggest recommendations for improving future clinic care.